Innovation diffusion during sustainable port development : How does technological and administrative innovation drive three dimensions of sustainability? - He, Pei-Yu (My University, 2023)
With the growing demands for seaborn trading and concerns of sustainability, maritime industry is facing a challenge. Port system as an important node between sea and land sides, development of port system can reinforce the sustainability of the port. Theoretical background shows that innovation diffusion can grant capabilities and competitiveness to the adopters to cope with complicated issues, such as three dimensions of sustainability (environmental, economic, and social). Innovation, such as administrative and technological innovations, are selected in this study since port operations consist of not only infrastructure but also management. The findings reveal that good coordination between administrative and technological innovation can effectively enhance three dimensions of sustainability. Meanwhile, there is a mutual needs for administrative and technological innovation. The outcomes of three dimensions of sustainability can vary due to the interrelationship between environmental, economic, and social dimensions.
Keywords: innovation diffusion, sustainability, port development